The Use of a Hybrid Pillar and Its Importance for Aesthetic Rehabilitation and Tissue Stability: A Clinical Report - Guilherme da Gama Ramos; Danilo Lazzari Ciotti; Samuel Rehder Wimmers Ferreira; Maide Rehder Wimmers Ferreira Margarido; Raquel Adriano Dantas; Marina Nottingham Guerreiro (Case Reports in Dentistry)
In the past, aesthetics had a secondary role in implant rehabilitation. Nowadays, the search for a perfect and harmonious aesthetic has stimulated the development of new materials and techniques. Due to this aesthetic requirement, the hybrid abutment (titanium link + zirconia) emerged as an alternative to metallic pillars. The hybrid abutment made a more favorable aesthetic possible, provided reliable mechanical properties, and increased biocompatibility to the surrounding tissues. Additionally, the individual zirconia abutment improves the emergency profile and the final white aesthetics. The objective of this paper is to report a clinical case with a manufactured individualized hybrid abutment for a metal-free indirect restoration, showing the applicability, mechanical properties, and biocompatibility of the hybrid abutment.